(untitled) (ҚазҰУ хабаршысы. Экология сериясы, 2016)
The data on current composition of ichthyofauna of the Zhem River are provided. By virtue of natural-geographic reasons and high anthropogenic load the breeding and development conditions of the fish remain difficult. The data on fish density distribution and their brief biological characteristics are provided.